Strategi Komunikasi Organisasi PT Tigamata Indonesia dalam Menjalin Hubungan dengan Pelanggan Periode Maret-Juni 2013 - Marta Sanjaya; Winki Octavianty (Humaniora, 2014)
PT. Tigamata Indonesia is a company engaged in the service of graphic design or creative industries. PT Tigamata Indonesia is not a new company, because before using the name of PT Tigamata Indonesia, this company has become a business entity that already has quite a lot of customer. Thus, PT. Indonesian Tigamata need public relations to manage communications with customers. The purpose of this study was to determine the public relations strategy of PT. Tigamata Indonesia in the communication between the company and the customer. The method used is qualitative-descriptive. Data were analyzed by using a technique that consists of data collection, data reduction, data display and conclusion. The results showed PT. Tigamata Indonesia has done public relations strategy in the form of communication through various media to build relationships with customers. The conclusion of this study is PT. Tigamata Indonesia has not reached a clear public relations strategy because of the lack of knowledge of the field of public relations company. It takes a more structured system of communication so that communication can be managed better and achieve maximum results. Therefore, PT. Tigamata Indonesia needs the concept of Customer Relationship Management (CRM) to enhance public relations strategy that is already owned by the company.